Can flavour and texture defects of plant-based burger patties be mitigated by combining them with a bun and tomato sauce? - Gonzalez-Estanol K; Orr RE; Hort J; Stieger M (Elsevier Ltd, 2023)
Common challenges for plant-based meat replacers are undesired (inherent) off-flavours (flavour defects) such as beany flavour or bitter taste, which are often associated with the use of plant proteins in meat replacers. Furthermore, plant-based meat replacers are often perceived as dry and lack juiciness and tenderness (texture defects). However, many foods are not consumed in isolation and sensory properties, and their acceptance, can be altered by the addition of other food components or condiments. The study aimed to compare the sensory properties and acceptance of commercially available plant-based burger patties eaten alone and in combination with other foods and/or condiments. Liking and sensory properties of a beef and two plant-based (soy and hemp) patties consumed alone, with a bun, with tomato sauce, and with a bun and tomato sauce were determined using a hedonic scale and Rate-All-That-Apply (RATA) methodology, respectively. For both plant-based patties (hemp, soy) bitter taste, beany and nutty flavour intensity remained but decreased with addition of a bun and/or sauce, but positive liking drivers such as meaty and fat flavour were also reduced. This suggests that these off-flavours can only be partly mitigated by the addition of a bun and/or sauce, but clearly cannot be masked completely. Hemp patties were perceived to have a high amount of chunks, which was a driver of disliking. This texture defect decreased with the addition of a bun and a bun with sauce. Off-flavours and texture defects of the hemp- and soy-based patties were too intense to be fully masked and could only be mitigated to a limited extent by the addition of a bun and/or tomato sauce. Notably, these reductions in off-flavour and texture defects were not sufficient to impact liking. The results highlight the importance of understanding product performance in realistic consumption scenarios. Addition of further ingredients and condiments, as is typical in a burger context, may be advantageous, but further research is required to test such a hypothesis.
Keywords: Composite foods; Plant-based; RATA